Cinematography. 16 mm film. Projector spools. Specification for spools for 16 mm motion-picture projectors (from 244 m to 610 m capacity: 24 cm to 38 cm size) Part 2.9.2, (29th August 1960) - British Standards Institution,
No abstract available